Preparation of cypress (Cupressus sempervirens L.) essential oil loaded poly(lactic acid) nanofibers - Argui Hayfa (De Gruyter, 2021)
This study investigated the production of poly(lactic acid) (PLA) nanofibers containing cypress (CUP) essential oil (EO) via electrospinning. The nanofibers were produced from polymer solution prepared with different percentages of cypress EO. Cypress EO-containing PLA nanofibers were characterized and some mechanical and thermal properties were examined using thermogravimetric analysis, scanning electron microscopy, Fourier-transform infrared spectroscopy, and dynamic mechanical analysis. The thermal stability of the nanofibers was reduced depending on the percentage of the cypress EO. As the ratio of the cypress EO to polymer matrices was increased, it was observed that the glassy transition temperatures of the nanofibers decreased and their flexibility increased. The T g value was determined to be 53.74°C for the neat PLA nanofiber, while 51.83°C for the PLA-CUP nanofiber (containing 15% cypress EO). According to the results of releasing trial, the increased amount of cypress EO resulted in less cypress EO releasing from polymer matrices. The nanofibers were observed to exhibit antibacterial activity against Escherichia coli and Staphylococcus aureus. The inhibition zone diameter of the nanofibers containing 10% cypress EO was 20 mm for S. aureus and 16 mm for E. coli, while 10 mm in the presence of Kanamycin.